Isolation, selection and characterization of cellulolytic fungi from cocoa (Theobroma cacao L) hull - Chafla, Ana L.; Rodríguez, Zoraya; Bocourt, Raúl; Espín, J.; Silva, Lucia (Cuban Journal of Agricultural Science, 2016)
The objective of this study was to isolate, select and characterize fungi with cellulolytic capacity from fresh cocoa hulls, in order to use them as inoculum for solid fermentation of fiber residues. For taking the sampled fruits, the five points method was applied on cocoa crops (creole variety), belonging to the Center of Research and Postgraduate Courses (CIPCA, initials in Spanish) from the Universidad Estatal Amazónica, Ecuador. Samples were ground and exposed to three collection environments, with records of contamination due to microorganisms. For selecting isolates, growth in the medium, macroscopic characteristics, cellulolytic activity, measured by digestion halos and power index were considered. Out of 68 isolates, 21 strains were previously selected from the environment with the highest microbial culture diversity. Cluster analysis was applied to the characteristics of the selected colonies, as well as analysis of the obtained dendrogram, and four groups were formed. With help of taxonomical keys, nine strains of Aspergillus, seven of Trichoderma, four of Chrysosporium and one of Fusarium were identified. The 47.62% of the strains showed the highest degradation halo, which belonged to Aspergillus (5), Chrysosporium (3) and Trichoderma (2) genera. Strains A8 of Aspergillus and T1 of Trichoderma showed the highest power index (2.88and 2.45respectively), so they can be considered for their industrial use or as inocula in solid state fermentation, in order to obtain enzymes or animal feeding. Key words: degradation halo, power index, Aspergillus, Trichoderma